Identifying Athlete's Majors and Career Aspirations: The Next Step in Clustering Research - Amanda L. Paule-Koba (Bowling Green State University, 2019)
The purpose of the study was to examine current collegiate athlete's academic majors and identify their career plans after graduation. The goal was to see if the athlete's academic major was congruent with their career aspirations. Previous research studies have shown that academic clustering, when 25% or more of an athletic team are in the same academic major, exists within a variety of athletic teams. However, there has not been a study done that assesses whether the athletes are majoring in disciplines that are related to their ultimate career goal. A total of 605 athletes from eight sports in the BIG10 and MAC conferences participated in the study. The results revealed that 192 of the 605 participants (31.7%) did not have majors and career aspirations that aligned. This study provides further insight into the academic puzzle of collegiate athletics.